2002
DOI: 10.1188/02.cjon.78-82
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for Head and Neck Surgery: A Patient-Education Tool

Abstract: Surgical treatment for head and neck cancer includes a variety of complex operative procedures. Patients scheduled for these operations often are presented with overwhelming amounts of information. Even after participating in the multidisciplinary, preoperative teaching process, they may be unable to fully comprehend the treatment plan. Pathways for head and neck surgery were designed to facilitate the patient- and family-education process and assist the patient in navigating through the surgical experience. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
1
10
0
Order By: Relevance
“…The median parity (minimum-maximum) was 1.0[1-4]. The other demographic characteristics were comparable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median parity (minimum-maximum) was 1.0[1-4]. The other demographic characteristics were comparable.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 215 women with one previous caesarean section were followed up using a standard care pathway. The median parity (minimum-maximum) was 1.0[ 1 - 4 ]. The other demographic characteristics were comparable.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that engagement strategies help patients feel empowered and have a sense of control over their recovery. 37 Our perioperative care pathway for microsurgical autologous breast reconstruction shows success in early and safe recovery. As a follow-up study, we are assessing the patient-reported outcomes regarding the quality of the patient’s recovery on the ERAS pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that some patients are unable to take part in decision‐making regarding treatment options because of difficulties understanding the necessary information. Clarke (2002) claims that ‘surgical treatment for head and neck cancer includes a variety of complex operative procedures. Patients scheduled for these operations often are presented with overwhelming amounts of information.…”
Section: Decision‐makingmentioning
confidence: 99%